OC-113 Contribution of home jejunostomy feeding in meeting energy and protein requirements in the months following oesophagogastric resection for cancer. (22nd June 2015) - Baker, M; Halliday, V; Ring, A; Bowrey, D
Abstract : Introduction: Nutritional intake is often compromised in the months following Oesophago-gastric resection. Studies evaluating the role of extended Jejunostomy feeding (JEJ) following hospital discharge are lacking. Method: As part of a randomised controlled feasibility study, investigating 6 weeks of home JEJ feeding, energy and protein intake were assessed using 3 day dietary records, analysed using Dietplan6®. Information on JEJ intake and body weight were collected for the same period. Nutritional requirements for energy (Henry equation adjusted for activity level) and protein (1.25 g/kg/d) were calculated. Oral intake was considered adequate if reported intake provided >75% of estimated requirements. Results: 54 participants were enrolled. There were 13 early withdrawals leaving 41 for analysis (Oesophagectomy, 32: Total Gastrectomy, 9). 20 participants were randomised to a planned program of home JEJ feeding providing ≥50% of energy and protein requirements, in addition to usual dietary intake. 21 participants in the control group received care as usual with JEJ feeding being stopped on hospital discharge, 7 of which (35%) had to recommence home feeding due to clinical and/or nutritional need. At 6 weeks post hospital discharge, oral energy intake was inadequate in 47% and 50% of the intervention and control group respectively. >5% weight loss was observed in 18/21 (86%) of the control group and 7/20 (35%) of the intervention group. Total calorie intake was adequate in the intervention group up to 3 months because of the contribution from JEJ feeding. Provision of JEJ did not seem to negatively impact on oral intake. At 3 and 6 months post-surgery, further weight loss was seen, and mean energy intakes did not meet 100% of estimated needs in the control group. Conclusion: This study has shown that oral energy/protein intakes are frequently inadequate in patients after Oesophagectomy/Total Gastrectomy and weight loss is observed. Supplementary JEJ feeding may make an important contribution to nutritional requirements and weight preservation in these early months. Further larger scale studies are required to fully evaluate this treatment. Disclosure of interest: M. Baker: None Declared, V. Halliday: None Declared, A. Ring: None Declared, D. Bowrey Grant/ Research Support from: Nutricia/Fresenius Kabi.